Metode dan Strategi Pembelajaran Menghafal Al-Qur’an di Rumah Tahfidz Khalifah Kota Probolinggo: Learning Methods and Strategies for Memorizing the Qur'an at Khalifah Tahfidz House, Probolinggo City - Achmad Fatahila; Habibi Muhammad, Devy (ISEDU : Islamic Education Journal, 2023)
The aim of this study was to obtain information regarding the methods and strategies used by the tahfidz house in memorizing the Koran for young children. This type of research is qualitative research. The research approach used by researchers is case studies. In qualitative research, researchers used interviews, questionnaires, tests and documentation. The results of this study are first, the methods applied by the tahfidz kholifah house include: the talaqqi method, the sima'i method, the tabarak method and the muraja'ah method. Second, the strategies implemented are divided into 2, namely teaching strategies in the form of strategies that pay attention to factors from within the child, because each teacher provides different strategies depending on the child's condition. And the second is the strategy applied by the students in memorizing, that is, there are differences between the students in the number of verses they want to memorize. The strategy used is almost the same as using electronic media, except that there are some students who use visual aids by reading the Koran. Third, the supporting factors for memorizing the Koran include: the spirit of the child, the teacher is a hafidz, adequate facilities and infrastructure, parental support. And the inhibiting factors: the child's ability to read the Koran, the child's concentration, the child's memory ability